Penggunaan Akun Twitter Sebagai Media Komunikasi Di Kalangan Penggemar Musik Korean HIP HOP - Cindrakasih, Roosita (LUGAS Jurnal Komunikasi, 2024)
Social media is media created to facilitate communication for humans. Twitter is one of the social media that is currently used by many people, not only to communicate but also to write opinions, to news. Fans as a community gather online through social media Twitter. These fans are joined in a community for the presence of a brand. Indonesia is ranked 1st as a country that talks about K-Pop on Twitter the most. Apart from talking about K-Pop, Twitter users also talk about other music genres such as Korean Hip-Hop. Base on social media Twitter, is an account that accommodates people who have the same interests to share information and communicate. The purpose of this study is to find out how social media Twitter becomes a medium of communication for fans of Korean Hip-Hop music. The research method used is a case study with a qualitative approach. The data analysis technique used in this study was by conducting interviews with six informants and one triangulator. The results of the study show that through User- Generated Content it produces an active community of Korean Hip-Hop music fans on the @khhfess account. That way the role of fans on the @khhfess account is very influential in the growth of the Korean Hip-Hop community on Twitter. This proves that Twitter social media can be the right communication medium for a community to discuss and share information.